Paper title greek yogurt with addition of tamarindo pulp: physical, chemical, microbiological and sensorial aspects (Research, Society and Development, 2020)
The objective of this work was to develop Greek yogurt with the addition of tamarind pulp and to characterize it through microbiological, sensory and physical-chemical analyzes. 3 formulations were prepared with different concentrations of tamarind pulp: 5% (Treatment 1), 10% (Treatment 2) and 15% (Treatment 3) of tamarind pulp. The products showed adequate sanitary quality without posing a risk to consumers. According to the ordering-preference test, 43.90% of the judges preferred treatment 1. Greek yogurt with the addition of 5% tamarind pulp showed good sensory acceptance in addition to being within the standards established by legislation regarding the levels of fat and proteins, however the acidity content was above the allowed, being necessary changes in the formulation for its adaptation to the Brazilian legislation.